Pengembangan Digitalisasi UMKM Sebagai Media Promosi Dan Pemasaran Produk Di Desa Banjaragung, Kecamatan Bareng, Kabupaten Jombang - Erin Dwi Cahyani; Jojok Dwiridotjahjono (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
In the current era, digital is very important and needed by every human being in their daily life, both for doing business and shopping. In the world of entrepreneurship, Micro, Small and Medium Enterprises (MSMEs) need digitization through social media so that the products that have been made can be recognized and marketed with a wider reach to consumers. However, the lack of knowledge regarding the use of social media is an obstacle for UMKM in Banjaragung Village so that marketing is carried out only offline and word of mouth. By conducting socialization and assistance regarding the functions and various features that can be used in social media to Banjaragung Village MSMEs, it is hoped that this can be implemented so that product marketing can be easier and optimal. The method used is qualitative with the type of data collection through observation, interviews, and documentation of activities. The results obtained from these activities are that UMKM in Banjaragung Village can utilize social media in marketing their products. So, having a social media account can be used as promotional media as well as product marketing by posting product photos and various other promos that can attract consumer interest.